2020
DOI: 10.1016/j.epsl.2019.115923
|View full text |Cite
|
Sign up to set email alerts
|

Core formation and geophysical properties of Mars

Abstract: The chemical and physical properties of the interiors of terrestrial planets are largely determined during their formation and differentiation. Modeling a planet's formation provides important insights into the properties of its core and mantle, and conversely, knowledge of those properties may constrain formational narratives. Here, we present a multi-stage model of Martian core formation in which we calculate core-mantle equilibration using parameterizations from high pressure-temperature metal-silicate part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 69 publications
(148 reference statements)
3
34
0
Order By: Relevance
“…There is a limited range (approximately IW-1.35 to IW-1.10) in which any analogs match Mars, regardless of other parameter values; even modestly 322 more reducing conditions result in a wide distribution of analog properties that extends to high 323 f Hf/W and ε182W, overshooting Mars. Fortunately, the average fO2 of core formation on Mars is constrained by its mantle FeO content (i.e., Equation 3), and previous studies have shown that the FeO-derived fO2 of Mars agrees with the permissible range found here (e.g., Righter & Drake, 1996;Rai & van Westrenen, 2013;Rubie et al, 2015;Brennan et al, 2020). Brennan et al (2020) also used mantle trace elements to constrain the values of Pfrac (0.4-0.6), kcore (0.84-1.0), and kmantle (0.4-1.0).…”
Section: Reproducing Marssupporting
confidence: 80%
See 1 more Smart Citation
“…There is a limited range (approximately IW-1.35 to IW-1.10) in which any analogs match Mars, regardless of other parameter values; even modestly 322 more reducing conditions result in a wide distribution of analog properties that extends to high 323 f Hf/W and ε182W, overshooting Mars. Fortunately, the average fO2 of core formation on Mars is constrained by its mantle FeO content (i.e., Equation 3), and previous studies have shown that the FeO-derived fO2 of Mars agrees with the permissible range found here (e.g., Righter & Drake, 1996;Rai & van Westrenen, 2013;Rubie et al, 2015;Brennan et al, 2020). Brennan et al (2020) also used mantle trace elements to constrain the values of Pfrac (0.4-0.6), kcore (0.84-1.0), and kmantle (0.4-1.0).…”
Section: Reproducing Marssupporting
confidence: 80%
“…Note that this approach is not self-consistent regarding the number of O atoms present in each protoplanet, but this is a negligible effect due to the lithophile character of O in Mars-sized bodies (e.g., Rubie et al, 2004;Steenstra & van Westrenen, 2018;Brennan et al, 2020). Ni was partitioned identically to Fe ( Ni = Fe ), S was approximated as perfectly siderophile, all other major elements (plus Hf) were assumed to be perfectly lithophile, and W partitioned between the core and mantle with its partition coefficient calculated as:…”
mentioning
confidence: 99%
“…If TiN is petrologically stable in regions of Earth's mantle, it would not be a buoyant phase, although it may be subject to entrainment (Lin & van Keken, 2006). We also compare the density of TiN to proposed density profiles for Venus (Aitta, 2012) and Mars (Brennan et al, 2020), finding that it is always denser than the mantles of both planets but less dense than their cores (Figure 4a). Compared to a selection of other naturally occurring nitrides (Fe 7 N 3 and Si 3 N 4 ), we find that TiN has an intermediate compressibility at room temperature (Figure 4b).…”
Section: Discussionmentioning
confidence: 93%
“…(a) TiN along a geotherm (J. Brown & Shankland, 1981) is significantly denser than Earth's mantle (Dziewonski & Anderson, 1981), as well as the mantles of Mars and Venus (Aitta, 2012; Brennan et al., 2020). TiN is less dense than planetary cores, however.…”
Section: Discussionmentioning
confidence: 99%
“…Highly and moderately siderophile elements (HSE and MSE, respectively) and Os isotopes are used to constrain processes such as accretion, mantle differentiation, crustal recycling, and core-mantle mixing, and the timing and depth of differentiation of Mars (Brandon et al, 2000;Walker 2009;Righter et al 2015). Righter et al (2015), Righter and Chabot (2011), Brennan et al (2020), Rai and van Westrenen (2013), and Yang et al (2015) showed that the MSE, HSE, and volatile contents of the Martian mantle (Brandon et al 2012;Yang et al 2015) could have been established by deep metal-silicate equilibrium in early Mars (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%